2022
DOI: 10.3171/2021.12.jns212869
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and complications of peripheral nerve field stimulation in the management of refractory trigeminal pain: a systematic review and meta-analysis

Abstract: OBJECTIVE Peripheral nerve field stimulation (PNFS) is a tool in the armamentarium of treatment options for trigeminal pain. The efficacy of this modality in mitigating trigeminal pain remains unclear. The aim of this study was to examine the existing literature on PNFS and elucidate pain score outcomes associated with its use in patients with trigeminal pain. METHODS A systematic review and meta-analysis was performed in accordance with the PRISMA framework. The PubMed, Web of Science, and Scopus databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…El 15 % de los pacientes con NT tienen esclerosis múltiple. La NT es muy bien diferencias de los demás dolores neuropáticos del nervio trigémino caracterizados por dolor neuropático, pero con un componente continuo, más quemante que paroxístico, y predominando la alodinia y la hiperalgesia sobre los puntos gatillo (1,(16)(17)(18).…”
Section: Definición De Términosunclassified
See 1 more Smart Citation
“…El 15 % de los pacientes con NT tienen esclerosis múltiple. La NT es muy bien diferencias de los demás dolores neuropáticos del nervio trigémino caracterizados por dolor neuropático, pero con un componente continuo, más quemante que paroxístico, y predominando la alodinia y la hiperalgesia sobre los puntos gatillo (1,(16)(17)(18).…”
Section: Definición De Términosunclassified
“…Los autores consideran que la estimulación del ganglio de gasser puede ser el futuro del tratamiento de los dolores neuropáticos del nervio trigémino, pero solo cuando se haya perfeccionado la técnica percutánea y, sobre todo, el sistema de anclaje del electrodo una vez posicionado en el cavum de Meckel a través del foramen oval. Igualmente, solo electrodos con tecnología wifi que no requieren cableado subcutáneo pueden tener futuro (1,18,31,32).…”
Section: Estimulación Del Ganglio De Gasserunclassified
“…The procedures related to neurostimulators are well tolerated, and the rate of surgical complications is generally relatively low. In previous studies, the rate of complications directly related to the surgery, like hemorrhage, lead malposition, or infections, in DBS was around 8–12% [18, 19] and for SCS and PNFS around 4–18% [20]. A device-related infection is among the most common complications.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear which therapeutic options may be offered to a patient with recurrent TN-either after previous MVD or after ablative surgery. While several studies have suggested percutaneous trigeminal ganglion ablation (by thermocoagulation, balloon compression or glycerol injection), radiosurgery, or peripheral nerve field stimulation [7,23,33,34], few other studies have advocated repeat microsurgical posterior fossa re-exploration.…”
Section: Introductionmentioning
confidence: 99%